1992
DOI: 10.1007/bf00182981
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment for acute rupture of the Achilles tendon

Abstract: Sixty-six patients with acute ruptures of the Achilles tendon were treated by immobilisation in a plaster cast for 12 weeks. Fifty-seven were followed up for a mean time of 70 months. Four re-ruptures occurred shortly after the initial treatment. Most patients had no or only slight complaints, three had moderate and one severe, problems. The activity level dropped slightly from 5.3 to 5.03 (Tegner score). The results are satisfactory with a low complication rate. The method is an alternative to operative repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…6,11 Nonetheless, there is no consensus on the immobilisation period for each of the 3 positions. 4,[12][13][14][15] In the current study, most respondents preferred to prescribe below-knee cast immobilisation followed by heel raises after cast removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11 Nonetheless, there is no consensus on the immobilisation period for each of the 3 positions. 4,[12][13][14][15] In the current study, most respondents preferred to prescribe below-knee cast immobilisation followed by heel raises after cast removal.…”
Section: Discussionmentioning
confidence: 99%
“…5 The re-rupture rate can be decreased from as high as 35% to 7% by increasing the immobilisation period from 8 to 12 weeks, as most re-ruptures occur within the first few weeks of cast removal. [6][7][8] The re-rupture rates have been reported to be 5% after using a plaster cast or the Sheffield splint, 9 but can be as high as 17% after plaster casting and as low as 0% after functional bracing. 10 We surveyed the practice of orthopaedic consultants in the Greater London area for treating Achilles tendon ruptures.…”
Section: Introductionmentioning
confidence: 99%
“…n Immobilization of both the knee and ankle has been the standard method of treatment for Achilles tendon rupture (Stein and Luekens 1976, Lennox et al 1980, Fruensgaard et al 1992. Some investigators have asserted that immobilization of the knee joint is not necessary for treatment (Beskin et al 1987, Carden et al 1987, and recent treatment trends are towards immobilization of only the ankle (Cetti et al 1993, Rantanen et al 1993, Soldatis et al 1997.…”
mentioning
confidence: 99%
“…Finally, several authors have recommended using an above the knee cast with a knee flexion to relax the gastrocnemius, which further reduces the gap distance. However, recent studies have indicated that tendon gap distance decreases by only 1 mm with a knee flexion in the order of 30°.…”
Section: Discussionmentioning
confidence: 99%